2017
DOI: 10.1167/iovs.16-21049
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Mutations in Known Mendelian Glaucoma Genes to Advanced Early-Onset Primary Open-Angle Glaucoma

Abstract: Citation: Zhou T, Souzeau E, Siggs OM, et al. Contribution of mutations in known Mendelian glaucoma genes to advanced early-onset primary openangle glaucoma. Invest Ophthalmol Vis Sci. 2017;58:153758: -154458: . DOI: 10.1167 PURPOSE. Primary open-angle glaucoma (POAG) and primary congenital glaucoma (PCG) with Mendelian inheritance are caused by mutations in at least nine genes. Utilizing whole-exome sequencing, we examined the disease burden accounted for by these known Mendelian glaucoma genes in a cohort o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…The Myocilin protein is encoded by the MYOC gene and is expressed widely in the body, including in skeletal muscle, heart, lung, pancreas, corpus ciliare, trabecular meshwork, and retina [15]. Current international work holds the MYOC mutation rate to be approximately 2-6% in POAG patients [5,16]. The MYOC Y437H mutation is located in the third exon of MYOC and was first reported in 1998 [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Myocilin protein is encoded by the MYOC gene and is expressed widely in the body, including in skeletal muscle, heart, lung, pancreas, corpus ciliare, trabecular meshwork, and retina [15]. Current international work holds the MYOC mutation rate to be approximately 2-6% in POAG patients [5,16]. The MYOC Y437H mutation is located in the third exon of MYOC and was first reported in 1998 [17].…”
Section: Discussionmentioning
confidence: 99%
“…Important risk factors for POAG include genetics, age, and environment. Previous reports have shown that gene mutations in MYOC, OPTN, and WDR36 are associated with the incidence of POAG [3][4][5]. Recently, we studied a large family from Hunan in China that had several members suffering from POAG.…”
Section: Introductionmentioning
confidence: 99%
“…JOAG is inherited mainly as a dominant trait with an onset age ranging from 3 to 35 years and characterized by high IOP requiring in most of the cases early surgical treatment. The major genetic players are mutations in MYOC with high prevalence and penetrance, followed by OPTN (optineurin) and WDR36 (WD repeat containing protein 36) ( 11 ). Aniridia is a very rare panocular disease whereby glaucoma is diagnosed in 50–70% of the cases at later ages (end of adolescent, early adulthood).…”
Section: Introductionmentioning
confidence: 99%
“…Five genes that cause POAG ( MYOC , OPTN , WDR36 , NTF4 , and TBK1 ) have been identified, but mutations in these genes cause disease in less than 10% of cases with POAG. [ 5 6 ] The combined effect of several genes and gene-environment interactions is expected to be important in the etiology of POAG in patients without mutations in the above-mentioned genes. [ 7 ] Genome-wide association studies and genetic studies of traits relevant to glaucoma, such as central cornea thickness, are useful for identifying genes that contribute to glaucoma in a non-Mendelian fashion.…”
Section: Introductionmentioning
confidence: 99%